Teacher early childhood education in the conditions of social change and educational. Start a professional-creating your own image by the teacher - Zamecka-Zalas, Olga (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The article concerns teacher’s professional start and his/her authority, creating the image. The issues discussed in the article are the relations between a pupil and a teacher. The problems described are the attitude of pupils towards the teacher, forms of authority observed at school, and difficulties and traps which can be encountered by a teacher at the beginning of his/her professional career.